Interrogating global narratives of trans queerness. Well-being and agency? Or more stories of trans trauma? - Vicars, Mark; Milenkovic, James (Frontiers in Sociology, 2024)
In the international contemporary discourse transgender individuals arguably have an increased presence within public media highlighting the visible diversity that constitutes the LGBTQI2S+ community. However, in response to the challenging of cisgendered normative assumptions there has been an unprecedented swathe of anti-trans measures executed through the frenzied repealing of rights and freedoms within the key arenas of legal, medical, sporting, and educative domains. This paper explores the intersections of pathologizing rhetoric that emplotted anti-trans and transphobic discourses within and across public consciousness. The quotidian presence of these discourses provoked in us a wondering about how evolving conceptual debate is constructing a trans inclusive global imaginary. In this paper we situate trans safety not as a singular concept, but rather a differentially experienced phenomenon that is related to and embedded in questions of bio power and privilege. As such, when we refer to a trans safety imaginary, we are not solely addressing protection from physical violence but also safeguarding against psychological and emotional vulnerability.